Molecular diversity and historical phylogeography of the widespread genus Mastiglanis (Siluriformes: Heptapteridae) based on palaeogeographical events in South America - Gales, Suellen M. (2021)
The catfish family Heptapteridae, endemic in the Neotropical region, is composed of small- to medium-sized species. The genus Mastiglanis was monotypic until very recently and is often misidentified as Imparfinis because of similarities in diagnostic characters, including the length of maxillary barbels and limited pigmentation. We provide the first molecular inference of diversity for samples identified as Mastiglanis. Partial 16S and COI sequences were produced for 84 samples identified morphologically as Mastiglanis from the Amazon, Orinoco and Essequibo river basins. Species delimitation and phylogenetic methods recovered the genus as monophyletic, but samples assigned to the species Mastiglanis asopos yielded 21 distinct operational taxonomic units, often in sympatry. The first cladogenesis event, at similar to 12 Mya, was associated with marine incursions and/or vicariance events between the northward-flowing systems in the west and the rivers that drain to the east. Subsequent diversification during the Miocene and Pliocene was inferred to have resulted from environmental changes associated with Andean orogeny, whereas recent diversification in the late Pliocene and Pleistocene was inferred to result from environmental changes during glacial cycles. Despite the many probable cryptic species found across the large geographical distribution of the genus, further sampling is expected to increase taxonomic richness in this genus.